Observance in the Implementation of Republic Act 7438 of the Arrested Suspect at Quezon City Police District Station 13 (Bagong Silangan) Police Substation: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This research paper Observes and analyzes the Implementation of Republic Act 7438, theright of the arrested suspect, detained or under custodial investigation, with the help of ourlocal authorities and community participants to ensure that the arrested suspect exercisestheir rights in Bagong Silangan Quezon City. To answer the problem, the researcher gathereddata with the help of questionnaires that detailed the rights of a suspect that should beexercised before and after arrest, detaining, and custodial investigation. The result alsorevealed that the Implementation of R.A 7438 has already been given and exercised to thesuspect who had been arrested. The implication of this study could be used to determine howR.A. 7438 helps the arrested suspect, detained or under custodial investigation, enjoy theirrights.The Data gathered by the researcher in the Implementation of Republic Act 7438 showed thatthe rights of the arrested suspect had already been exercised by the Quezon City PoliceDistrict Station 13 (Bagong Silangan) Police Substation. Most of the respondents, includingthe citizen of Bagong Silangan Quezon City, agree that the QCPD Station 13 exercised theImplementation of R.A 7438.
Keywords: Criminology